Biomaterial-based strategies for maxillofacial tumour therapy and bone defect regeneration - Tan, Bowen; Tang, Quan; Zhong, Yongjin; Wei, Yali; He, Linfeng; Wu, Yanting; Wu, Jiabao; Liao, Jinfeng (International journal of oral science, 2021)
Issues caused by maxillofacial tumours involve not only dealing with tumours but also repairing jaw bone defects. In traditional tumour therapy, the systemic toxicity of chemotherapeutic drugs, invasive surgical resection, intractable tumour recurrence, and metastasis are major threats to the patients’ lives in the clinic. Fortunately, biomaterial-based intervention can improve the efficiency of tumour treatment and decrease the possibility of recurrence and metastasis, suggesting new promising antitumour therapies. In addition, maxillofacial bone tissue defects caused by tumours and their treatment can negatively affect the physiological and psychological health of patients, and investment in treatment can result in a multitude of burdens to society. Biomaterials are promising options because they have good biocompatibility and bioactive properties for stimulation of bone regeneration. More interestingly, an integrated material regimen that combines tumour therapy with bone repair is a promising treatment option. Herein, we summarized traditional and biomaterial-mediated maxillofacial tumour treatments and analysed biomaterials for bone defect repair. Furthermore, we proposed a promising and superior design of dual-functional biomaterials for simultaneous tumour therapy and bone regeneration to provide a new strategy for managing maxillofacial tumours and improve the quality of life of patients in the future.